Halal Logo Verification Device - Shayfull Zamree, Abd. Rahim; Abdul Rahman, Mohd Saad, Prof. Madya; Mohd. Azaman, Md. Deros; Mohd. Sazli, Saad; Muhamad Farizuan, Rosli (Universiti Teknologi MARA, Kedah, 2010)
Invention, Innovation & Design (IID Kedah 2010), 28th - 29th July 2010 organized by Universiti Teknologi MARA (UiTM), Kedah at SP Inn, Kedah.